Pengaruh Capital Expenditure, Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Rahmiati, Rahmiati; Sari, Widya (Jurnal Kajian Manajemen Bisnis, 2013)
The purpose of this research is to analyze the influence of Capital Expenditure, capital structure and profitability to firm value (Price to Book Value) on Manufacturer company which listed on Indonesian stock exchange. This research include to causative research. Research sample was chosen by purposive sampling method and research period in 2006 untill 2009, so the sample of this research is 106 companies. The kind of data is secondary data from www.idx.co.id. Analysis method is double linear regression. Hyphotesis test use t statistic test. The result of this research shows that Capital Expenditure (Ln Capital Expenditure Ratio) and Profitability (Ln ROE) that impact to firm value (Ln Price to Book Value). Meanwhile, capital structure (Ln LTDER) can not influence firm value (Ln Price to Book Value).